Insight into particle retention and clogging in porous media; a pore scale study using lattice Boltzmann method. (April 2020) - Parvan, Amin; Jafari, Saeed; Rahnama, Mohammad; Norouzi apourvari, Saeid; Raoof, Amir
Highlights: Simulation particle transport using Lattice Boltzmann Method. Introduce a new method to deposition fine particles in porous media. Investigation of clogging process in real porous media. Investigation the influence of initial porosity and topology on coefficients of porosity-permeability relation. Abstract: Particle deposition in porous media alters hydraulic properties including porosity and permeability. The extent of these alterations depends on both porous media structure and its geometrical and topological properties. In the present study, a Lattice Boltzmann modeling is developed and used to systematically simulate particle clogging and to explore the evolution of hydraulic properties using realistic pore structures obtained from x-ray tomography. A total of six different porous media are studied where three domains have different porosities and grain sizes, but the same pore connectivities, to explore the geometrical effects, and three domains have the same porosity but different grain arrangements and pore connectivities to study the effect of porous media topology. The results have shown the impact of the underlying pore-scale mechanisms resulting in porous media clogging and how they are affected by the initial porosity and topology of the media. Moreover, simulation has been utilized to develop porosity-permeability relations, covering the initial sample permeability all the way to complete clogging of the media where permeability vanishes. To provide more generic relations, the obtained coefficients of the porosity-permeability formulations are correlated to each porous media geometrical and topological properties.